The bacterial type III-secreted protein AvrRps4 is a bipartite effector. - Morgan K Halane; Sang Hee Kim; Benjamin J Spears; Christopher M Garner; Conner J Rogan; Elizabeth C Okafor; Jianbin Su; Saikat Bhattacharjee; Walter Gassmann (PLoS Pathogens, 2018)
Bacterial effector proteins secreted into host plant cells manipulate those cells to the benefit of the pathogen, but effector-triggered immunity (ETI) occurs when effectors are recognized by host resistance proteins. The RPS4/RRS1 pair recognizes the Pseudomonas syringae pv. pisi effector AvrRps4. AvrRps4 is processed in planta into AvrRps4N (133 amino acids), homologous to the N-termini of other effectors including the native P. syringae pv. tomato strain DC3000 effector HopK1, and AvrRps4C (88 amino acids). Previous data suggested that AvrRps4C alone is necessary and sufficient for resistance when overexpressed in heterologous systems. We show that delivering AvrRps4C from DC3000, but not from a DC3000 hopK1- strain, triggers resistance in the Arabidopsis accession Col-0. Delivering AvrRps4C in tandem with AvrRps4N, or as a chimera with HopK1N, fully complements AvrRps4-triggered immunity. AvrRps4N in the absence of AvrRps4C enhances virulence in Col-0. In addition, AvrRps4N triggers a hypersensitive response in lettuce that is attenuated by coexpression of AvrRps4C, further supporting the role of AvrRps4N as a bona fide effector domain. Based on these results we propose that evolutionarily, fusion of AvrRps4C to AvrRps4N may have counteracted recognition of AvrRps4N, and that the plant RPS4/RRS1 resistance gene pair was selected as a countermeasure. We conclude that AvrRps4 represents an unusual chimeric effector, with recognition in Arabidopsis by RPS4/RRS1 requiring the presence of both processed effector moieties.